Dorsal root ganglia P2X4 and P2X7 receptors contribute to diabetes-induced hyperalgesia and the downregulation of electroacupuncture on P2X4 and P2X7 - Qun-qi Hu; Xiao-fen He; Yi-qi Ma; Li-qian Ma; Si-ying Qu; Han-zhi Wang; Yu-rong Kang; Lu-hang Chen; Xiang Li; Bo-yu Liu; Xiao-mei Shao; Jun-fan Fang; et al. (Purinergic Signalling, 2023)

MicroRNA: Crucial modulator in purinergic signalling involved diseases - Jing Guo; Peng Yang; Yi-Fan Li; Jin-Fan Tang; Zhao-Xuan He; Shu-Guang Yu; Hai-Yan Yin (Purinergic Signalling, 2023)
Both microRNAs (miRNAs) and purinergic signalling are widely and respectively expressed in various tissues of different organisms and play vital roles in a variety of physiological and pathological processes. Here, we reviewed the current publications contributed to the relationship of miRNAs and purinergic signalling in cardiovascular diseases, gastrointestinal diseases, neurological diseases, and ophthalmic diseases. We tried to decode the miRNAs-purinergic signalling network of purinergic signalling involved diseases. The evidence indicated that more than 30 miRNAs (miR-22, miR-30, miR-146, miR-150, miR-155, miR-187, etc.) directly or indirectly modulate P1 receptors (A 1 , A 2A , A 2B , A 3 ), P2 receptors (P2X1, P2X3, P2X4, P2X7, P2Y2, P2Y6, P2Y12), and ecto-enzymes (CD39, CD73, ADA2); P2X7 and CD73 could be modulated by multiple miRNAs (P2X7: miR-21, miR-22, miR-30, miR-135a, miR-150, miR-186, miR-187, miR-216b; CD73: miR-141, miR-101, miR-193b, miR-340, miR-187, miR-30, miR-422a); miR-187 would be the common miRNA to modulate P2X7 and CD73.

Purinergic ATP triggers moxibustion-induced local anti-nociceptive effect on inflammatory pain model - Hai-Yan Yin; Ya-Peng Fan; Juan Liu; Dao-Tong Li; Jing Guo; Shu-Guang Yu (Purinergic Signalling, 2023)
Purinergic signalling adenosine and its A1 receptors have been demonstrated to get involved in the mechanism of acupuncture (needling therapy) analgesia. However, whether purinergic signalling would be responsible for the local analgesic effect of moxibustion therapy, the predominant member in acupuncture family procedures also could trigger analgesic effect on pain diseases, it still remains unclear. In this study, we applied moxibustion to generate analgesic effect on complete Freund’s adjuvant (CFA)-induced inflammatory pain rats and detected the purine released from moxibustioned-acupoint by high-performance liquid chromatography (HPLC) approach. Intramuscular injection of ARL67156 into the acupoint Zusanli (ST36) to inhibit the breakdown of ATP showed the analgesic effect of moxibustion was increased while intramuscular injection of ATPase to speed up ATP hydrolysis caused a reduced moxibustion-induced analgesia. These data implied that purinergic ATP at the location of ST36 acupoint is a potentially beneficial factor for moxibustion-induced analgesia.

Purinergic P2X7 receptor functional genetic polymorphisms are associated with the susceptibility to osteoporosis in Chinese postmenopausal women - Hong Xu; Chengxin Gong; Luling He; Shenqiang Rao; Xingzi Liu; Yijun Nie; Changle Liu; Tao Li; Lu Ding; Yunming Tu; Yuping Yang; Fangfang Hu; et al. (Purinergic Signalling, 2017)

Inhibitory effect of estrogen receptor beta on P2X3 receptors during inflammation in rats - Qian Jiang; Wen-xin Li; Jia-run Sun; Tian-tian Zhu; Juan Fan; Li-hua Yu; Geoffrey Burnstock; Hua Yang; Bei Ma (Purinergic Signalling, 2017)

LncRNA NONRATT021972 siRNA attenuates P2X7 receptor expression and inflammatory cytokine production induced by combined high glucose and free fatty acids in PC12 cells - Hong Xu; Luling He; Changle Liu; Lan Tang; Yonghu Xu; Mengqi Xiong; Mei Yang; Yongfang Fan; Fangfang Hu; Xingzi Liu; Lu Ding; Yun Gao; et al. (Purinergic Signalling, 2016)

Sensory–sympathetic coupling in superior cervical ganglia after myocardial ischemic injury facilitates sympathoexcitatory action via P2X7 receptor - Jun Liu; Guilin Li; Haiying Peng; Guihua Tu; Fanjun Kong; Shuangmei Liu; Yun Gao; Hong Xu; Shuyi Qiu; Bo Fan; Qicheng Zhu; Shicheng Yu; et al. (Purinergic Signalling, 2013)

Estrogen modulation of peripheral pain signal transduction: involvement of P2X3 receptors - Bei Ma; Li-hua Yu; Juan Fan; Binhai Cong; Ping He; Xin Ni; Geoffrey Burnstock (Purinergic Signalling, 2011)